1967
DOI: 10.1515/znb-1967-0105
|View full text |Cite
|
Sign up to set email alerts
|

Pulsradiolytische Untersuchung von Dimethylthioäther und Dimethylsulfoxyd in wäßriger Lösung

Abstract: The following absolute rate constants of the reactions of eaq⊖ and OH with dimethylthioether and dimethylsulfoxide have been determined: k (eaq⊖ + CH3SCH3) =2.0·107 mol-1 l sec-1; k(e⊖+ CH3SOCH3) =1.7·106; k(OH+CH3SCH3) =5.2·109; k(OH+CH3SOCH3) =4.2·109. The acid and basic components of the equilibriumare formed in the reactions of OH+CH3SCH3 and eaq⊖ +CH3SOCH3, respectively. The anion absorbs at 3500 Å. The ρK value of the equilibrium was found to be equal to 10.2. The CH2SCH3 radical (2900 Å) and the ions CH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
2

Year Published

1973
1973
2003
2003

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(34 citation statements)
references
References 0 publications
4
28
2
Order By: Relevance
“…The most studied reactions are those with OH, a key gas phase and aqueous phase atmospheric oxidant. Several studies of the OH + DMSO reaction have been reported (Meissner et al, 1967;Reuvers et al, 1973;Veltwisch et al, 1980;Milne et al, 1989;Bardouki et al, 2002) which are in good agreement, suggesting a room temperature rate coefficient in the range of (6 ± 2) ¥ 10 9 M -1 s -1 . One study of the OH + DMSO2 reaction (Milne et al, 1989) reports a relatively slow rate coefficient of 3.0 ¥ 10 7 M -1 s -1 .…”
Section: Introductionsupporting
confidence: 54%
See 1 more Smart Citation
“…The most studied reactions are those with OH, a key gas phase and aqueous phase atmospheric oxidant. Several studies of the OH + DMSO reaction have been reported (Meissner et al, 1967;Reuvers et al, 1973;Veltwisch et al, 1980;Milne et al, 1989;Bardouki et al, 2002) which are in good agreement, suggesting a room temperature rate coefficient in the range of (6 ± 2) ¥ 10 9 M -1 s -1 . One study of the OH + DMSO2 reaction (Milne et al, 1989) reports a relatively slow rate coefficient of 3.0 ¥ 10 7 M -1 s -1 .…”
Section: Introductionsupporting
confidence: 54%
“…Room temperature (295 K) rate coefficients determined in this study are compared with literature values in Table 2. All data summarized in Meissner et al, 1967;2. Reuvers et al, 1973;3.…”
Section: Comparison With Previous Workmentioning
confidence: 99%
“…The formation of SO, indicates that the addition pathway is not necessarily related only to the formation of CH,SO,H, but could also lead to the production of SO, as well. The same reaction has been studied by Meissner et al (1967) in aqueous solutions of sulfoxides and a YIN, DANIEL GROSJEAN, AND JOHN H. SEINFELD similar reaction rate constant of 1.2 X lo-" cm3 molecule-' s-l has been reported (Gilbert et al, 1975a). While CH,S(O)CH, and CH,S(O),CH, may react with a number of radicals in the atmosphere, their reaction with OH is likely to be the most important chemical loss process, and their reactions with NO, could also be important at nighttime in the atmosphere.…”
Section: Reaction Of Chs(o) Chmentioning
confidence: 97%
“…At a mole fraction of 0.017 the rate constant is 2.9 x lo6 M-' s-' but the rate constant seems to be decreasing as the concentration of DMSO decreases. Meissner et al (36) reported a value of 1.7 x lo6 M -I s-' for the reaction of es-with DMSO in alkaline solutions of DMSO slightly more dilute than 0.017 mole fraction.…”
Section: Resultsmentioning
confidence: 98%